POLITIK HUKUM NASIONAL UNDANG-UNDANG NOMOR 12 TAHUN 2010 TENTANG GERAKAN PRAMUKA YANG BERASASKAN PEMBANGUNAN - Kamizi, Fajar; Hadi, Abdul (Muamalah, 2019)
Legal politics is understood as the Legal Policy or policy direction taken by the government in making and implementing the rule of law to achieve the goals of the state. The legal politics of Law Number 12 of 2010 concerning the Scouting Movement, in which the Law was born in response to the Government and the Parliament is to revitalize the Scouting Movement which is expected to be a vehicle for the formation of national identity, the spirit of nationalism, and patriotism for the people of Indonesia. However, this has not yet had a positive impact and is in line with expectations. Laws that have a strategic role in the implementation of the goals and ideals of the nation and state should be formed with clear objectives, appropriate formulations, have legal certainty, sustainability, harmony and harmony. so that a law that is formed in a long period of time can last and in accordance with the conditions of the future community by always referring to the National Long-Term Development Plan that is structured in a directed and systematic manner as a national legal politics that has been established based on Pancasila and the Basic Law Negara Republik Indonesia in 1945. National legal politics towards the Scout Movement is a Progressive law that is influenced by changes in social conditions in society.